Life Style Diseases and Its Cure through Yoga Practices - Menon, Sreekumar D.; Manoj K. A. (Advancement and New Understanding in Medical Science Vol. 8, 2024)
The concept of yoga practicing in our daily life is a holistic approach towards health as well as an alternative form of medicine. Advances in medical sciences and better living conditions have increased the life expectancy. Biological ageing is correlated with increased morbidity, mortality and poor health states. This together with changing lifestyles and urbanization has brought a radical shift in the types of health problem being faced by populations in the developing world giving rise to an epidemic of chronic diseases. Life style means a pattern of individual practices and personal behavioral choices that are related to elevated or reduced health risk. Lifestyle diseases or diseases of civilization are diseases that appear to increase in frequency as countries become more industrialized and people live longer. They can include Heart disease, Diabetes, Stroke, Alzheimer's, Cirrhosis, Asthma, Hypertension etc. These are caused to a large extent by dietary changes in relation to socio- economic and living environmental conditions. The stress of modern living is causing an enormous burden on health care globally. Poor eating habits sleep deprivation and secondary lifestyles have contributed to the growth of lifestyle diseases. This diseases also sometimes called as western diseases or diseases of affluence, non communicable diseases (NCD) or regenerative diseases. Hypertension is associated with the incidence of some diet-related non-communicable diseases such as stroke and coronary heart diseases. Lifestyle diseases are different from other diseases because they are potentially preventable, and can be lowered with changes in diet, lifestyle, and environment and by supplements with vitamin D. The study was conducted among 60 participants who came for practicing yoga and having regular attendances. According to WHO, the world’s deaths from lifestyle diseases will double by 2015 unless all-out effort is taken to combat them. As per WHO) latest /recent) report 41 million people killed every year due to noncommunicable diseases (NCD’s) which is roughly 74% of all deaths globally. Main causes /reasons for these lifestyle diseases are Habits, Unhealthy lifestyles/Behaviors and Practices. In another way we can say smoking, drinking, drugs, exposure to pollution in home or in work place, shortage of physical activities, poor or unhealthy eating habits, lack of taking nutritive value foods, shortage in taking water, high stress level, less sleep etc. Yoga is the re-union of mind and body to God. Depending upon the way in which it is practiced it can be divided into several types like ”Khada yoga”, ”Dhyana yoga”, “Raja yoga”, ”Sidha yoga ” etc. Normally Indians practice Khada yoga (hatha yoga). It is nothing but bending and stretching of the bodies. This is the only exercise which starts and ends with a prayer to God. Yoga practice imparts positive energy to us. It will give a energy throughout life. The study concluded that yoga practice is effective for reduce hyper tension. Most of the life style disease can be controlled by practicing yoga.